COMMUNICATION OPPORTUNITIES OF MODERNISM IN THE SYSTEM OF MASS COMMUNICATION IN THE SYRIAN ARAB REPUBLIC. PART TWO - Oksana Kosiuk (Інтегровані комунікації)
The second part of the research continues the study of current problems of modern Syrian painting as a means of communication with the help of the goal was set to explore the visual arts of modern Syria as a means and method of communication with the help of structuralism (distinguishing the directions, methods and styles of modernism), semiotic and content analyzes (identifying symbolic units of communication), comparison (studying the process and experiences), modeling (defining the features of movements, directions and styles), etc.